Analisis Studi Komparasi Metode Pembelajaran Problem Based Learning (PBL) Dan Contextual Teaching And Learning (CTL) Terhadap Pencapaian Prestasi Belajar Ekonomi Siswa Kelas XI SMA N 1 Mejayan - Tutik Tutik (GHAITSA : Islamic Education Journal, 2020)
The purpose of this study was to determine whether there were differences in the effect between the learning method PROBLEM BASED LEARNING (PBL) and CONTEXTUAL TEACHING AND LEARNING (CTL) on the achievement of economic learning competence on the subject of tax for high school students in class XI semester 1. This study used a real experimental method (CTL) true experimental research). The study population was all students of class XI of SMA N 1 Mejayan, consisting of 5 classes, with many students in each class of 40 to 45 students. Samples were taken by cluster sampling technique of 2 classes, the selected class is XI Social Sciences 2 class as experimental class I and XI Social Sciences 3 as experimental class II. Data collection techniques using the test method. Testing the requirements analysis of the normality test used the Shapiro Wilk method and the homogeneity test used the Levene method. The data analysis technique used is the t test. Based on the results of the study it can be concluded: There is a difference in the effect between the learning method PROBLEM BASED LEARNING (PBL) with the method of learning CONTEXTUAL TEACHING AND LEARNING (CTL) on the achievement of economic learning achievement on the subject of tax for high school students in class XI semester 1. This is indicated by the value of t arithmetic of -11.215 at a significant level of 0.05 that is equal to 0.041 so that the significant value is smaller than 0.05 (probability 0.041 <0.05). The average change in economic learning achievement on the subject of tax for PBL class is 1.68 and for CTL class is 3.03. Therefore, the CONTEXTUAL TEACHING AND LEARNING (CTL) method is more influential in improving learning achievement.